Penggunaan Lembar Kerja Siswa (LKS) untuk Menigkatkan Hasil Belajar Kognitif Materi Bangun Ruang Sisi Lengkung pada Peserta Didik Kelas IX-B SMP XYZ Sentani Papua [Using Student Worksheets to Increase Cognitive Achievement of Curve Sides of Three Dimensional Space Figures of Grade IX-B Students at XYZ Junior High School in Sentani, Papua] - Kornelius Kristian Wardana Putra; Pingkan Wuisan; Tanti Listiani (Universitas Pelita Harapan, 2016)
The problem faced by the students in grade IX-B SMP XYZ in Sentani, Papua is the low achievement of cognitive learning, especially in math. Factors affecting low cognitive achievement are internal and external. Seeing the problem at hand, the researcher tried to solve it by using student worksheets as a medium to improve cognitive learning outcomes. The purpose of the research is to determine whether there is an increase in cognitive achievements of students using student worksheets and to know how to use the student worksheet to help the students achieve the cognitive learning outcomes. The research methodology used was Class Action Research (CAR) that lasted for two cycles. The research was carried out in grade IX-B at XYZ Junior High School in Sentani, Papua from August 26, 2015 until November 13, 2015. The research instruments used were student assesment worksheets, written test sheets, observation sheets, questionnaire sheets, and interview sheets. Based on the results of the research, using student worksheets has not improved the cognitive learning outcomes of the students between cycle 1 and cycle 2. There was a decline in the percentage of cognitive learning outcomes of students in the second dimension of the cognitive process (understanding). However, the results suggest that the overall use of student worksheets can improve the cognitive learning process of students.BAHASA INDONESIA ABSTRAK: Permasalahan yang ada pada peserta didik kelas IX-B SMP XYZ Sentani, Papua adalah rendahnya pencapaian hasil belajar kognitif khususnya pelajaran matematika. Faktor-faktor yang mempengaruhi rendahnya hasil belajar kognitif berasal dari dalam dan luar diri peserta didik. Dari permasalahan yang ada, maka diberikan solusi dengan menerapkan penggunaan lembar kerja siswa (LKS) sebagai media pembelajaran dalam meningkatkan hasil belajar kognitif. Tujuan penelitian ini untuk mengetahui apakah terdapat peningkatan hasil belajar kognitif peserta didik melalui penggunaan media lembar kerja siswa (LKS) dan untuk mengetahui cara penggunaan media lembar kerja siswa (LKS) dalam membantu peserta didik mencapai hasil belajar kognitif. Metode penelitian yang digunakan adalah metode penelitian tindakan kelas (PTK) yang berlangsung selama dua siklus. Penelitian dilaksanakan di SMP XYZ Sentani, Papua kelas IX-B tanggal 26 Agustus 2015 hingga 13 November 2015. Instrumen penelitian yang digunakan berupa lembar penilaian LKS, lembar tes tertulis, lembar observasi, lembar angket, dan lembar wawancara. Berdasarkan hasil penelitian, penggunaan media lembar kerja siswa belum dapat meningkatkan pencapaian hasil belajar kognitif peserta didik dari siklus 1 ke siklus 2. Terjadi penurunan presentase pencapaian hasil belajar peserta didik pada dimensi proses kognitif kedua (memahami). Akan tetapi secara keseluruhan penggunaan LKS dapat meningkatkan proses belajar kognitif peserta didik.